Laboratory evolution of adenylyl cyclase independent learning in Drosophila and missing heritability. (19th June 2014) - Cressy, M.; Valente, D.; Altick, A.; Kockenmesiter, E.; Honegger, K.; Qin, H.; Mitra, P. P.; Dubnau, J.
Abstract : Gene interactions are acknowledged to be a likely source of missing heritability in large‐scale genetic studies of complex neurological phenotypes. However, involvement of rare variants, de novo mutations, genetic lesions that are not easily detected with commonly used methods and epigenetic factors also are possible explanations. We used a laboratory evolution study to investigate the modulatory effects of background genetic variation on the phenotypic effect size of a null mutation with known impact on olfactory learning. To accomplish this, we first established a population that contained variation at just 23 loci and used selection to evolve suppression of the learning defect seen with null mutations in the rutabaga adenylyl cyclase. We thus biased the system to favor relatively simplified outcomes by choosing a Mendelian trait and by restricting the genetic variation segregating in the population. This experimental design also assures that the causal effects are among the known 23 segregating loci. We observe a robust response to selection that requires the presence of the 23 variants. Analyses of the underlying genotypes showed that interactions between more than two loci are likely to be involved in explaining the selection response, with implications for the missing heritability problem. Abstract : Missing heritability is prevalent in a laboratory selection with just 23 segregating loci and full genotyping.